Stability Study of Anticancer Agent N-[(Hexahydroazepin-1-yl)methyl]daunorubicin in Aqueous Solutions Using HPLC Method - Zalewski, Przemyslaw; Zajac, Marianna; Jelinska, Anna; Cielecka-Piontek, Judyta; Oszczapowicz, Irena (Asian Journal of Chemistry, 2010)
A high performance liquid chromatographic method with UV detection (254 nm), which has been applied for the determination of N-[(hexahydroazepin-1-yl)methyl]daunorubicin (HMD), is described. The samples of solution were chromatographed on LiChrospher RP 18 e column (125 mm × 4 mm, particle size 5 mm), using an eluent composed of: 9 volumes of acetonitrile, 1 volume of methanol and 10 volumes of a solution containing 2.88 g L-1 of sodium lauryl sulfate and 1.6 mL L-1 of phosphoric(V) acid. The method was validated with respect to selectivity, linearity and precision. The method was found appropriate for kinetic studies of the stability of N-[(hexahydroazepin-1-yl)methyl]daunorubicin (HMD) in aqueous solutions in the range pH 0.43-13.71. The pH-rate profile indicated (a) hydrolysis of protonated molecules of HMD depending on hydrogen ions and (b) spontaneous hydrolysis under the influence of water depending on the substrate charge. General acid-base hydrolysis of HMD was observed in phosphate (pH 1.89-3.10) and acetate (pH 4.01-5.65) buffers. The ionic strength effect and thermodynamic parameters of the reaction were determined.